Meaning : Semantics, p.ragramatics, Cognition ([Place of publication not identified] : Routledge Taylor and Francis Group., 2023)
Betty Brner's new book is an ideal guide for students' magical mystery tour of the fascinating intricacies of p.rogramatics and semantics p.roffesor birner clearly introduces landmark research in linguistics p.hilosop.hy and other relevant discip.linees insp.iring and help.ing students begin exp.loring meaning language connections for themselves sally Mccnnell ginet linguistics cornell university usa
index:p..295-301
Keywords: Cognition; p.ragramatics; Semantics